The Return of "Patrimonial Capitalism" : Review of Thomas Piketty's Capital in the 21st Century - Milanovic, Branko (World Bank Group, Washington, DC, 2014)
The paper provides a detailed review of Thomas Piketty's book "Capital in the 21st century." It focuses on the new contributions of the book, and in particular on its unified treatment of economic growth, functional income distribution, and concentration of personal income. It concludes that Piketty's reinvigoration of classical and empircally-drven approach is likely to have a profound impact on economics.